(untitled) (The Review of Diabetic Studies, 2024)
Background: Herpes zoster (HZ), commonly referred to as shingles, results from the reactivation of the varicella-zoster virus (VZV). This is the identical pathogen responsible for varicella, also known as chickenpox. Initially, VZV infection leads to varicella. Subsequently, post-varicella, VZV enters a dormant state within the dorsal root ganglia. As individuals age or experience immunosuppression, their cell-mediated immunity to the VZV diminishes, leading to the reactivation of VZV and the onset of zoster, or shingles, which can manifest anywhere on the body. its prevalence in Saudi Arabia is not well established. Vaccination remains a key public health strategy, yet vaccine uptake varies widely. Its prevalence and severity underscore the importance of effective vaccination strategies. Vaccination against HZ has emerged as a crucial public health intervention. In the Kingdom of Saudi Arabia, the prophylactic HZ vaccine which has been licensed is the recombinant subunit glycoprotein E vaccine which is called SHINGRIX. Aim of the study: This study aims to assess the Knowledge about the Herpes Zoster (HZ) Vaccine and Its Acceptance among the Population in the Kingdom of Saudi Arabia 2024 addressing a significant gap in current research. Methods: A cross-sectional study was conducted at patients with history among the herpes zoster visiting the primary health sector in Saudi Arabia, from May to October 2024, 300 patients were included and data were collected by using a data were collected using an adapted questionnaire distributed via Google forms written questionnaire. Results: shows that most of the participants (50.0%) were in the age group (40-49) years , gender the majority of them male was higher compared to female(66.0% and 34.0%) , nationality the majority of participant are Saudi were(82.0%) , the marital status most of participants married were(74.0%) Conclusion: The study highlights a significant gap in knowledge and low vaccine uptake among the target population in Saudi Arabia . It underscores the need for educational initiatives and awareness programs to improve understanding and acceptance of the HZ vaccine. These findings can inform healthcare providers and policymakers in developing strategies to enhance vaccination coverage and ultimately improve public health outcomes in the region.